2015
DOI: 10.1002/2015jc011103
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of nutrient concentrations in the Mediterranean Sea: Contribution of Bio‐Argo floats

Abstract: In 2013, as part of the French NAOS (Novel Argo Oceanic observing System) program, five profiling floats equipped with nitrate sensors (SUNA‐V2) together with CTD and bio‐optical sensors were deployed in the Mediterranean Sea. At present day, more than 500 profiles of physical and biological parameters were acquired, and significantly increased the number of available nitrate data in the Mediterranean Sea. Results obtained from floats confirm the general view of the basin, and the well‐known west‐to‐east gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 97 publications
4
40
1
Order By: Relevance
“…In the Mediterranean Sea, Lavigne et al (2013) showed that in the south Ionian Sea and in the Levantine Sea, the probability that the MLD reaches the nitracline depth is very low. These results were corroborated by a recent analysis based on Bio-Argo floats (Pasqueron de Fommervault et al, 2015). However, in regions where mesoscale circulation is cyclonic (e.g., south Adriatic gyre, Rhodes gyre), there is evidence of surface nutrient enrichment caused by vertical mixing (Gačić et al, 2002;Lascaratos et al, 1993;Salihoglu et al, 1990).…”
Section: Role Of the Nig Circulation Patterns Compared To The Interansupporting
confidence: 77%
See 1 more Smart Citation
“…In the Mediterranean Sea, Lavigne et al (2013) showed that in the south Ionian Sea and in the Levantine Sea, the probability that the MLD reaches the nitracline depth is very low. These results were corroborated by a recent analysis based on Bio-Argo floats (Pasqueron de Fommervault et al, 2015). However, in regions where mesoscale circulation is cyclonic (e.g., south Adriatic gyre, Rhodes gyre), there is evidence of surface nutrient enrichment caused by vertical mixing (Gačić et al, 2002;Lascaratos et al, 1993;Salihoglu et al, 1990).…”
Section: Role Of the Nig Circulation Patterns Compared To The Interansupporting
confidence: 77%
“…From nitrate concentration profiles, the nitracline depth was estimated as the depth of the 1 µM isoline (Cermeño et al, 2008;Lavigne et al, 2013;Pasqueron de Fommervault et al, 2015) and compared to the depth of the 28.9 kg m −3 isopycnals (Fig. 3c).…”
Section: In Situ Datamentioning
confidence: 99%
“…The method is based on the Owens and Millard (1985) algorithm that has been slightly adapted by Sea-Bird in the data processing software using a hysteresis correction (Sea-Bird Scientific, 2014). A new set of calibration coefficients for this sensor was determined after the cruise; it was used to post-process the whole data set.…”
Section: Data Processingmentioning
confidence: 99%
“…In turn this sinking of OM could explain its reduction in surface layers, together with decreases in bacteria and viruses, thought by the authors to have been filtered from the water by the sinking MOAs. Thus soot (and black carbon), as well as desert dusts (Pasqueron de Fommervault et al, 2015) may control foam and whitecap production globally by two mechanisms: foam destabilization; and reduction of surface OM concentrations by sticking to and ballasting MOAs, thus producing or increasing their sinking.…”
Section: Long-lived Foaming Eventsmentioning
confidence: 99%